Product certification as a tool for the development of craft food production (Economics and region, 2025)
Every year, the demand for high-quality craft food products from local producers is increasing. Consumers are paying more attention to products that are produced with minimal use of industrial methods, focusing on the naturalness of ingredients, their local origin, and the uniqueness of the production process. This trend promotes the development of craft food production, which uses traditional recipes and technologies. However, the definition of craft food products is not regulated by law in Ukraine, leading to the misuse of this term by dishonest producers to attract consumers’ attention to their products. This approach not only misleads consumers but also undermines trust in genuine craft producers, creating a negative effect on the market. Therefore, it is important to analyze the role of craft product certification in ensuring the development of craft food production. Certification provides an opportunity to distinguish products made using traditional methods from mass-produced foods, which are made in large factories with automated processes. Defining clear criteria for certification will create standards that match the specifics of craft production. The key attributes of craft food production have been identified, which should be considered when developing criteria for certifying craft foods. Taking these attributes into account when developing certification standards will help ensure that only genuine craft foods have the right to certification. Craft food certification will protect consumers from counterfeit products and confirm that the product meets established quality and safety standards. The presence of a certificate gives the consumer additional confidence that the product is made according to standards that ensure its safety and high quality. Certification will also increase the competitiveness of products in the marketplace, as certified products will stand out from competitors who do not have such certification. This will allow craft producers to more easily enter new markets, both national and international. Moreover, certification will promote the development of craft production by encouraging producers to adhere to high standards, which will contribute to improving the overall quality of products.
Keywords: craft production; craft producer; craft product certification; craft production attributes; product origin